POLA DINAMIS DISTRIBUSI BERAS UNTUK OPERASI PASAR DOlOG BENGKUlU - Nufus, Nurhayatin (Jurnal AGRISEP, 2006)
This research  aimed  to analyze  the  moving  average  of rice distribution  and the  effect  of four decompositon  components  for market operation  along  1995 - 2001 period.  The results show that dinamic distribution  pattern  based  on syclicaJ trend tends  to increasing  along with consumption.  There were two clearly variations  first quarter / and IV with higher distribution  index and quarter 1/  and III with lower index. Under  quarter  I and IV known  as deficit  the planting  season,  while quarter  1/   and III known as harvest season where as the people has plenty of stock in cyl/os. Finally the random component (/) was iffluenced much to the distribution pattern,it  was relevance  to goverment policy to ruie the rice policy and distrbution.